Green-synthesized natural antioxidants in poultry and livestock feed: enhancing oxidative stability and animal welfare - Nefzi, Khaoula; BenSouf, Ikram; Saidani, Mariem; Darej, Cyrine; Bejaoui, Bochra; Ben Larbi, Manel; M’Hamdi, Naceur; Lequart, Vincent; Joly, Nicolas; Martin, Patrick (Frontiers in Veterinary Science, 2026)
Oxidative stress, caused by an imbalance between reactive oxygen species and antioxidant defenses, significantly impacts livestock health, welfare, and productivity. Green synthesis has emerged as a sustainable approach for enhancing the stability and bioavailability of natural antioxidants in animal feed. Unlike conventional extraction methods, green-synthesized antioxidants derived from plant extracts, essential oils, and agro-industrial by-products offer improved oxidative stability, reduced toxicity, and enhanced bioactivity. These bioengineered antioxidants not only mitigate oxidative stress but also support immune function, improve feed efficiency, and enhance meat quality by reducing lipid peroxidation and increasing vitamin E content. Furthermore, the incorporation of green-synthesized antioxidants in livestock nutrition contributes to environmentally friendly production practices, aligning with sustainable agriculture and consumer demand for natural animal products. This review examines the potential of green-synthesized antioxidants, their role in improving oxidative stability, and their impact on animal welfare, performance, and product quality.